Disease Mechanisms of C9ORF72 Repeat Expansions - Gendron, Tania F. (Cold Spring Harb Perspect Med, 2018)
G(4)C(2) repeat expansions within the C9ORF72 gene are the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). These bidirectionally transcribed expansions lead to (1) the accumulation of sense G(4)C(2) and antisense G(2)C(4) repeat-containing RNA, (2) the production of proteins of repeating dipeptides through unconventional translation of these transcripts, and (3) decreased C9ORF72 mRNA and protein expression. Consequently, there is ample opportunity for the C9ORF72 mutation to give rise to a spectrum of clinical manifestations, ranging from muscle weakness and atrophy to changes in behavior and cognition. It is thus somewhat surprising that investigations of these three seemingly disparate events often converge on similar putative pathological mechanisms. This review aims to summarize the findings and questions emerging from the field’s quest to decipher how C9ORF72 repeat expansions cause the devastating diseases collectively referred to as “c9ALS/FTD.”